Berberine Inhibits FOXM1 Dependent Transcriptional Regulation of POLE2 and Interferes With the Survival of Lung Adenocarcinoma - Ni, Lulu; Sun, Ping; Fan, Xiaochun; Li, Zhongjie; Ren, Hongli; Li, Jiangan (Frontiers in Pharmacology, 2022)
Background：Berberine is one of the most interesting and promising natural anticancer drugs. POLE2 is involved in many cellular functions such as DNA replication and is highly expressed in a variety of cancers. However, the specific molecular mechanism of berberine interfering with POLE2 expression in lung adenocarcinoma (LUAD) is still unknown to a great extent. Method:The KEGG database (Release 91.0) and Gene Ontology (GO) category database were used for functional annotation of differentially expressed genes after berberine treatment. Reproducibility assessment using TCGA dataset. The biological functions of berberine in LUAD were investigated by a series of in vitro and in vivo experiments: MTT, colony formation, mouse xenograft and plasmid transfection. The molecular mechanisms of berberine were demonstrated by plasmid transfection, quantitative RT-PCR and Western blotting. Result:The elevated expression of FoxM1 and the high enrichment of DNA replication pathway were confirmed in LUAD by microarray and TCGA analysis, and were positively correlated with poor prognosis. Functionally, berberine inhibited the proliferation and survival of LUAD cell lines in vitro and in vivo. Mechanistically, berberine treatment down regulated the expression of FoxM1which closely related to survival, survival related genes in cell cycle and DNA replication pathway, and significantly down regulated the expression of survival related POLE2. Interestingly, we found that the transcription factor FoxM1 could act as a bridge between berberine and POLE2. Conclusion: Berberine significantly inhibited LUAD progression via the FoxM1/POLE2, and FoxM1/POLE2 may act as a clinical prognostic factor and a therapeutic target for LUAD. Berberine may be used as a promising therapeutic candidate for LUAD patients.